American koan: imagining Zen and self in autobiographical literature - Van Overmeire, Ben (Studies in religion and culture, 2024)
Preface -- Acknowledgments -- Note on Language Conventions -- Introduction -- 1. Enlightenment: D. T. Suzuki and Philip Kapleau -- 2. Failure: Janwillem Van de Wetering, David Chadwick, Natalie Goldberg, Shozan Jack Haubner -- 3. The Two Truths: Myoan Grace Schireson, Claire Gesshin Greenwood, Zenju Earthlyn Manuel -- 4. Detachment in Van de Wetering's Afterzen -- 5. Interdependence in the Work of Ruth Ozeki -- 6. Conclusion -- Notes -- Bibliography -- Index.